O processual na cena contemporânea: práticas de criação e poéticas teatrais que enfatizam o percurso e a experiência da Cia. Luna Lunera na gênese de "Prazer" - Soraya Beatriz Luciano Silva (2014)
The objective of this research is to discuss the relevance of the procedural dimension assumed in creative practices and in contemporary poetics, in a context where the focus on the artistic journey, rather than the result of the performance, is valued in its ontological specificity of the theatrical phenomenon, assuming a substantially unfinished nature. From a literature review, we seek to demonstrate that, with the birth of the twentieth century and the idea of a renovation of the theater, the creative process has taken a key aspect in the theater thinking of the main creators of the period, shifting his gaze to the stage testing, through the creation and research in studios and, in the second half of the century, in the theatrical laboratories. This research assumes the view that the need to reinvent the theater and, consequently, the actor, created in these practices a unique relationship with space, time, research and the final work. This paradigm shift has as one of its offshoots, including in Brazil, the emergence of collective and collaborative practices of theatrical creation. We intend to demonstrate that that such practices appropriate the concepts of dramaturgy in process and tend to generate whose poetic primacy lies in unstable formulations and displacement result for the creative route. In light of such evidence in the contemporary scene procedural and allied research practice of genetic criticism and criticism of creative process, this dissertation also seeks to understand the procedural dimension from the collaborative experience of Cia Luna Lunera and intend to show, in the creative process of Pleasure, the procedures that focus on the journey and the ways in which the final work preserves traces of its construction.